1978
DOI: 10.1128/aac.14.5.659
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Chemotherapy and Immune Defenses in Experimental Murine Cryptococcosis

Abstract: Congenitally athymic nude (nu/nu) and thymus-containing heterozygous (nu/X) mice were infected intraperitoneally with Cryptococcus neoformans over a wide range of challenge doses. Cryptococcal disease progressed more rapidly in nude mice than in their nu/X littermates. When nu/X mice were treated with amphotericin B, all survived an otherwise lethal dose of C. neoformans. At larger challenge doses, survival was prolonged in nu/nu mice treated with amphotericin B, but they later succumbed to cryptococcosis. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…This issue is relevant to the mechanism of AMB antifungal action, since this drug has a large volume of distribution and its concentration in tissue may be below the fungicidal threshold (5-7, 12, 18). In this regard AMB has been shown to be relatively ineffective against C. neoformans in nude mice, suggesting that its direct antifungal effects alone are insufficient to modify infection in severely immunocompromised hosts (9). Our results showing a change in cryptococcal cellular morphology imply that indirect mechanisms are important factors in the activity of AMB.…”
mentioning
confidence: 49%
“…This issue is relevant to the mechanism of AMB antifungal action, since this drug has a large volume of distribution and its concentration in tissue may be below the fungicidal threshold (5-7, 12, 18). In this regard AMB has been shown to be relatively ineffective against C. neoformans in nude mice, suggesting that its direct antifungal effects alone are insufficient to modify infection in severely immunocompromised hosts (9). Our results showing a change in cryptococcal cellular morphology imply that indirect mechanisms are important factors in the activity of AMB.…”
mentioning
confidence: 49%
“…In addition to demonstrating the efficacy of KY-62, these results are of interest because they highlight the importance of host immune status rather than serum concentration in distinguishing the drugs. In studies of murine cryptococcosis and histoplasmosis, we have found that immunosuppressed (athymic) mice respond less well to antifungals than do immunocompetent mice (6,7,23). The present studies suggest that a decreased response to at least some antifungals may be present in neutropenic mice with candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal host defense against C. neoformans undoubtedly involves interaction between phagocytes and immunoregulatory lymphocytes [9,12,16,25,26]. The crucial role of T cells in defense against C. neoformans has been well established by the markedly increased susceptibility to lethal infection of inbred mice with genetic deficiencies of T cell function [11,20,[27][28][29]. The relative contributions of individual T cell subtypes, are being assessed using the technique of in vivo subset depletion by monoclonal antibody treatment.…”
Section: Discussionmentioning
confidence: 99%